1982
DOI: 10.1111/j.1432-1033.1982.tb05779.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence and Secondary Structure of Citrus Exocortis and Chrysanthemum Stunt Viroid

Abstract: The complete nucleotide sequence of citrus exocortis viroid (CEV, propagated in Gymura) and chrysanthemum stunt viroid (CSV, propagated in Cineraria) has been established, using labelling in vilro and direct RNA sequencing methods and a new screening procedure for the rapid selection of suitable RNA fragments from limited digests.The covalently closed circular single-stranded viroid RNAs consist of 371 (CEV) and 354 (CSV) nucleotides, respectively. As previously shown for potato spindle tuber viroid (PSTV, 359… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0
6

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(119 citation statements)
references
References 38 publications
2
110
0
6
Order By: Relevance
“…The length of the gene (304 bp) correlates well with the length of the RNA suggesting that the gene for the 7S RNA does not contain intron(s) although extremely small introns (less than 10 bp) can not be excluded by these data. This was further confirmed by sequencing fragments of 7S RNA obtained by partial digestion of this RNA with RNases U2, Ti and A (21,22,23). These partial RNA sequences covered 92 % of the total DNA sequence identified as the gene for the 7S RNA without any interruption.…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…The length of the gene (304 bp) correlates well with the length of the RNA suggesting that the gene for the 7S RNA does not contain intron(s) although extremely small introns (less than 10 bp) can not be excluded by these data. This was further confirmed by sequencing fragments of 7S RNA obtained by partial digestion of this RNA with RNases U2, Ti and A (21,22,23). These partial RNA sequences covered 92 % of the total DNA sequence identified as the gene for the 7S RNA without any interruption.…”
Section: Methodsmentioning
confidence: 72%
“…Isolation of DNA was carried out as previously described (9 (20) and Gross et al (21). Partial enzymatic digestion of RNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis demonstrated that the nucleic acid detected in broad bean was a variant of CEVd containing 373 nucleotides with ten differences as compared with CEVd-C (Fig. 2a, b) (Gross et al, 1982). Six of these variations (see asterisks in Fig.…”
Section: Identification Of a C E V D Variant In Broad Beanmentioning
confidence: 99%
“…Moreover, the characterization of most viroids, including CEVd, has been accomplished after their purification from alternative herbaceous hosts which provided high viroid titres (Semancik & Weathers, 1972;Gross et al, 1982;Visvader et al, 1982). Since the viroid population of a given isolate can be modified as a result of host and tissue selection its biological properties may also vary depending on the host chosen for its characterization (Semancik et al, 1993).…”
Section: Introductionmentioning
confidence: 99%